Brain metastases from non-small cell lung cancer: molecular subtypes and emerging CNS-directed precision therapies - Sharma, Mehek; Shah, Anvay; Rivera-Caraballo, Kimberly A.; Raval, Girindra; Kaur, Balveen; Wallace, Gerald C. (Frontiers in Oncology, 2026)
Non-small-cell lung cancer (NSCLC) is a leading cause of morbidity and mortality globally, due in large part to the development of NSCLC-associated brain metastases (L-BM). Upon initial presentation, 11-26% of patients with NSCLC will have L-BM, while half of patients with NSCLC will develop L-BM over the course of their disease. The emergence of PD-1/PD-L1 immunotherapy and targeted therapies for EGFR, ALK, and ROS1 mutations has transformed the treatment landscape and improved outcomes for select patient populations. CNS progression remains a major challenge due to therapy resistance, the blood–brain barrier (BBB), and the unique molecular and transcriptomic adaptations exhibited by NSCLC brain metastases which differs markedly from primary lung tumors. In this review, we examine the molecular drivers of CNS metastasis, oncogenic signaling-targeted therapies, and next-generation CNS drug-delivery strategies including intraventricular or intranasal administration, focused ultrasound, nanocarriers, and efflux transporter modulation. Furthermore, we provide a comprehensive update on recent and ongoing preclinical and clinical studies, highlighting novel CNS-penetrant agents with demonstrated intracranial efficacy. Understanding these mechanisms and refining targeted approaches are critical to improving CNS disease control, survival outcomes, and quality of life for NSCLC patients with brain involvement.